Controllable synthesis of mesoporous SBA-15 using H2SO4. (4th May 2021) - Xian, Qiang; He, Xinmiao; Chen, Li; Wang, Enchao; Dan, Hui; Ding, Yi
ABSTRACT: Mesoporous SBA-15 has been synthesised using a binary acid H2 SO4 as media. The effects of H2 SO4 concentration and synthesis temperature on the morphologies and mesostructures of the obtained mesoporous SBA-15 materials were studied. The results revealed that the more-ordered structure was obtained at a H2 SO4 concentration of 2 M, while a higher H2 SO4 concentration of 3 M led to a less-ordered structure. In addition, with increasing H2 SO4 concentration from 1 to 3 M, the morphologies of SBA-15 particles transferred from rod-like to sphere-like. This work demonstrated that mesoporous SBA-15 with various textural properties and morphologies can be feasibly obtained by controlling the H2 SO4 concentration and synthesis temperature.